A comparative performance analysis of direct, with battery, supercapacitor, and battery-supercapacitor enabled photovoltaic water pumping systems using centrifugal pump. (1st September 2018) - Das, Madhumita; Mandal, Ratan
Highlights: Periodic fluctuation of solar radiation cause problem in centrifugal pumping operation. Steady power is required to supply to the pumping system for avoiding pump transients. Therefore proper research work/study is required to sort out the problem. Authors tried to tackle the problem by providing different system configuration. A new approach is made towards studying different configurations of SPVWPS with battery and super capacitors under varying discharge pressure and evaluate the performance parameters. Four different configurations of SPVWPS using centrifugal pump are considered, namely, directly coupled, with battery, with the super capacitors and with a battery-super capacitor hybrid, to determine the optimum configuration for higher system performance. The experiment have been carried out on a small scale SPVWPS with 2 m and 3 m dynamic head. Abstract: To operate centrifugal pump against higher discharge pressure and to achieve specific speed for delivering the water, the level of irradiance required is quite high. Therefore, by knowing the operating pressure this problem may be minimized by using energy storage devices like battery or supercapacitor operated in parallel with the SPV module. Here is the need to select a proper configuration of solar PV water pumping system (SPVWPS) using energy storage devices for the economic application. Therefore, a new approach is made towards studying different configurations of 7SPVWPS with battery and supercapacitors under varying discharge pressure and evaluate the performance parameters. Four different configurations of SPVWPS using centrifugal pump are considered, namely, directly coupled, with battery, with the supercapacitors and with a battery-supercapacitor hybrid, to determine the optimum configuration for higher system performance. The experiment have been carried out on a small scale SPVWPS with 2 m and 3 m dynamic head of the pump on sunny days at Haldia, India. The comparison of the performance for the different configurations have been reported. The study reveals that the supercapacitor based configuration give highest instantaneous efficiency. The centrifugal pump powered by SPVWPS using battery delivers a maximum of 2964 L per day for 2 m dynamic head whereas for 3 m dynamic head SPVWPS using supercapacitor delivers a maximum of 1826 L per day. An economic comparison is also done for the different topologies.